Deep Immune Phenotyping and Single-Cell Transcriptomics Allow Identification of Circulating TRM-Like Cells Which Correlate With Liver-Stage Immunity and Vaccine-Induced Protection From Malaria - Noé, Andrés; Datoo, Mehreen S.; Flaxman, Amy; Husainy, Mohammad Ali; Jenkin, Daniel; Bellamy, Duncan; Makinson, Rebecca A.; Morter, Richard; Ramos Lopez, Fernando; Sheridan, Jonathan; Voukantsis, Dimitrios; Prasad, Naveen; et al. (Frontiers in Immunology, 2022)
Protection from liver-stage malaria requires high numbers of CD8+ T cells to find and kill Plasmodium-infected cells. A new malaria vaccine strategy, prime-target vaccination, involves sequential viral-vectored vaccination by intramuscular and intravenous routes to target cellular immunity to the liver. Liver tissue-resident memory (TRM) CD8+ T cells have been shown to be necessary and sufficient for protection against rodent malaria by this vaccine regimen. Ultimately, to most faithfully assess immunotherapeutic responses by these local, specialised, hepatic T cells, periodic liver sampling is necessary, however this is not feasible at large scales in human trials. Here, as part of a phase I/II P. falciparum challenge study of prime-target vaccination, we performed deep immune phenotyping, single-cell RNA-sequencing and kinetics of hepatic fine needle aspirates and peripheral blood samples to study liver CD8+ TRM cells and circulating counterparts. We found that while these peripheral ‘TRM-like’ cells differed to TRM cells in terms of previously described characteristics, they are similar phenotypically and indistinguishable in terms of key T cell residency transcriptional signatures. By exploring the heterogeneity among liver CD8+ TRM cells at single cell resolution we found two main subpopulations that each share expression profiles with blood T cells. Lastly, our work points towards the potential for using TRM like cells as a correlate of protection by liver-stage malaria vaccines and, in particular, those adopting a prime-target approach. A simple and reproducible correlate of protection would be particularly valuable in trials of liver-stage malaria vaccines as they progress to phase III, large-scale testing in African infants. We provide a blueprint for understanding and monitoring liver TRM cells induced by a prime-target malaria vaccine approach.